Data Centers and beyond, Optical Fiber Communications Breakthroughs from OFC 2019. Issue 3 (4th May 2019) - Hodara, H.; Mitchell, G.
ABSTRACT: Fiber-optic communication breakthroughs are presented every year at the Optical Communication Conference, OFC. This paper reviews some of the key papers presented at the OFC 2019, held March 3 through 7 in San Diego, CA. Some of the conference themes were: Data Center Connectivity, 5G Networks, and major advances in components and in communication systems. The Conference stressed the work carried out by the Optical Internetworking Forum, OFI, which developed the 400 ZR standard for 400 Gigabit fiber modules. This standard enables interoperability between transceiver manufacturers. (See link:https://www.oiforum.com/technical-work/hot-topics/400zr-2/ )